Auditing Fair Value Estimates in Developing Countries: The Case of Jordan - Abdullatif, Modar (Asian Journal of Business and Accounting, 2016)
Manuscript type: Research paper Research aims: This study explores the main issues faced by external auditors in Jordan when auditing fair value estimates, and examines the reasons causing these issues, and their effects on the conduct of auditing. Design/Methodology/ Approach: This study employs a qualitative approach, using semi-structured interviews with a sample comprising of experienced Jordanian auditors from the Big Four audit firms, other internationally-affiliated audit firms, and local Jordanian audit firms. Research findings: The findings of this study show that fair value estimates have been aggressively used by some companies to overvalue their assets, especially in the areas of asset impairment and business combinations. Factors facilitating this include the lack of reliable fair value information and the weak corporate governance system. Auditors face extensive pressure from clients to accept questionable fair value estimates in an environment of low demand for high-quality audits, low audit fees, and the fear of losing clients. Auditors are also under the pressure of regulatory authorities to improve the quality of their work. Theoretical contributions/ Originality: The auditing of fair value estimates is an empirically under-researched area in developing countries. The introduction of International Financial Reporting Standard (IFRS) 13 (Fair Value Measurement) places the demand that an estimate of fair value has to be reported when needed, regardless of the level of available information or market activity. Conducting a study in a developing country with an environment that is characterised by inactive markets, limited available information on fair values, and low demand for high-quality audits, can further contribute to knowledge on how fair value estimates are audited under different circumstances to those of developed countries. Practitioner/ Policy implications: The findings of this study show that there is a need for regulatory authorities to put in more efforts to scrutinise the behaviour of auditors and audit clients when dealing with fair value estimates. The regulatory authorities also need to improve the conditions auditors face when auditing these estimates. Such improvements could include increasing the monitoring of fair value specialist evaluators, revising audit fee levels, and revising corporate governance regulations. Research limitations/ Implications: This study focuses on the Jordanian environment. By expanding the research to other developing countries, and by focusing in detail on some of the issues studied in developed countries (such as how auditors assess management’s assumptions regarding fair value estimates, and how they develop their own independent estimates), a better understanding of these issues in the developing country contexts can be gained, benefitting the audit profession and contributing to literature at the same time. Keywords: Auditing, Developing Countries, Fair Value Estimates, Jordan. JEL Classification: M42